Ontogenetic changes in the modulation of taste aversion learning by home environmental cues in rats - Infurna, R N; Steinert, P A; Spear, N E (Journal of comparative & physiological psychology, 1979)
Eight experiments using 611 rats as subjects were conducted to define and analyze an age-related phenomenon of conditioned taste aversion. When consumption of sucrose solution was followed by LiCl-induced illness in the animals' home, acquisition of the aversion to sucrose solution was retarded in preweanling (18-day-old) rats. This effect was not found in adults or in slightly older (21-day-old) rats. Place of testing had no effect in the younger two age-groups, but in adults manifestation of the acquired aversion was retarded when they were tested in the home. There was no interaction between place of conditioning and testing for any age. The locus of the environmental influence on conditioning in preweanling rats was found to be the place of tasting rather than place of illness, retention interval, or testing. Also, the effect was found to be invariant under minor variations in familiarization of the animal with the non-home environment. The principle emerging from these data and others is that the home environment can have a significant influence on learning and conditioning in the immature rat.